Characteristics Of The Demographic Development Of Cis: A Case Study Of Uzbekistan - Xudaybergenovich, Abduramanov Xamid (European Scientific Journal, ESJ, 2016)
This article gives a specified place of population of the Republic of Uzbekistan among the CIS countries. A dynamics of the population of the Republic of Uzbekistan for 1991-2015 was obtained. Also, an analysis of the structure of the population according to number, age and distribution was carried out. The determined factors affecting the age structure of the population was also ascertained. Demographic pressure factor was calculated. A long-term demographic forecast of Uzbekistan was carried out for the period until 2030. The territory of the Republic of Uzbekistan and the CIS countries were divided into groups according to the level of ageing population. They developed scientifically based proposals and recommendations towards improving the welfare of elderly people on the basis of the current demographic situation in Republic of Uzbekistan.